2020
DOI: 10.3389/fpls.2020.587641
|View full text |Cite
|
Sign up to set email alerts
|

Embryo-Endosperm Interaction and Its Agronomic Relevance to Rice Quality

Abstract: Embryo-endosperm interaction is the dominant process controlling grain filling, thus being crucial for yield and quality formation of the three most important cereals worldwide, rice, wheat, and maize. Fundamental science of functional genomics has uncovered several key genetic programs for embryo and endosperm development, but the interaction or communication between the two tissues is largely elusive. Further, the significance of this interaction for grain filling remains open. This review starts with the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 62 publications
0
32
0
Order By: Relevance
“…1). Since the formation of chalky tissue is a result of incomplete accumulation of starch and protein, it is tempting to speculate that the embryo plays a role in it, probably by depriving the nutrients from its proximate bottom endosperm (An et al, 2020). As revealed by our previous studies, the embryo demonstrated a negative effect on the contents of proteins, amino acids, and minerals in the chalky endosperm (Lin et al, 2016;Lin et al, 2017).…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…1). Since the formation of chalky tissue is a result of incomplete accumulation of starch and protein, it is tempting to speculate that the embryo plays a role in it, probably by depriving the nutrients from its proximate bottom endosperm (An et al, 2020). As revealed by our previous studies, the embryo demonstrated a negative effect on the contents of proteins, amino acids, and minerals in the chalky endosperm (Lin et al, 2016;Lin et al, 2017).…”
Section: Introductionmentioning
confidence: 91%
“…In addition, this comparison method revealed that the influence of embryo on IAA was (Ebisuya and Briscoe, 2018). There is evidence of bidirectional 4 interaction between embryo and endosperm throughout development (An et al, 2020).…”
mentioning
confidence: 88%
See 3 more Smart Citations